TARAS SHEVCHENKO IS IN FATE OF OLGA DUCHYMINSKA - Kisіl, І. V.; Pakhomov, V. M. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The influence of Taras Shevchenko on the works of author Olha Duchyminska is retraced in the article.